2019
DOI: 10.1007/s11262-019-01634-6
|View full text |Cite
|
Sign up to set email alerts
|

Nasal virome of dogs with respiratory infection signs include novel taupapillomaviruses

Abstract: Using viral metagenomics, we characterized the mammalian virome of nasal swabs from 57 dogs with unexplained signs of respiratory infection showing mostly negative results using the IDEXX Canine Respiratory Disease RealPCR™ Panel. We identified canine parainfluenza virus 5, canine respiratory coronavirus, carnivore bocaparvovirus 3, canine circovirus and canine papillomavirus 9. Novel canine taupapillomaviruses (CPV21-23) were also identified in 3 dogs and their complete genome sequenced showing L1 nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…According to the literature, CPV 9 and CPV 15 have only been reported in benign lesions [20,52]. In the present study, CPV 9 was identified in a dog with multiple cutaneous neoplasms, including multiple skin papillomas, cutaneous horn, and SCCs (case no.…”
Section: Discussionsupporting
confidence: 49%
“…According to the literature, CPV 9 and CPV 15 have only been reported in benign lesions [20,52]. In the present study, CPV 9 was identified in a dog with multiple cutaneous neoplasms, including multiple skin papillomas, cutaneous horn, and SCCs (case no.…”
Section: Discussionsupporting
confidence: 49%
“…Carnivora host-associated papillomaviruses belong to the genera Chi -, Lambda -, Tau -, Omega -, Treiseta -, Dyotheta - and Dyonupapillomavirus . The most studied PVs of Carnivora hosts are from domestic dogs (types CPV1—CPV23), belonging to the genera Chi -, Lambda - and Taupapillomavirus [ 8 , 13 , 26 ]. Within the mustelids, PVs have only been reported in southern sea otters infected with Enhydra lutris papillomavirus 1 (ElPV1), which causes oral papillomatosis [ 56 ], and in fecal material from a ferret infected with Mustela putorius papillomavirus 1 (MpPV1) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…PVs have been found not only in mammals, but also in fish [ 19 ], birds [ 20 , 21 , 22 ] and reptiles [ 23 , 24 ]. The most studied PVs in animals are from domestic hosts, including cattle [ 7 , 8 , 25 ], dogs [ 8 , 26 ], cats [ 8 , 27 , 28 ], horses [ 29 , 30 ], and sheep [ 31 , 32 ]. In addition to domestic animals, PVs have also been studied in various wildlife hosts, such as the ocelot [ 33 ], bottlenose dolphin [ 34 ], gray wolf [ 35 ], red fox [ 36 ], European badger [ 37 ], tree shrew [ 38 ], giant panda [ 39 ], roe and red deer [ 40 , 41 , 42 , 43 , 44 , 45 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Viral pathogens are the main cause of CIRD, with common causes including canine coronavirus (CCoV), canine parainfluenza virus, canine adenovirus type 2 (CAV-2) and canine distemper virus. However, emerging respiratory viruses have been continuously found in dogs, including severe acute respiratory syndrome coronavirus 2 and canine taupapillomavirus (Altan et al, 2019;Sit et al, 2020). To date, the viruses associated with CIRD remain unclear in China and require further study.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, CPnV and DogPyV were first detected in China. Recently,Altan et al (2019) have characterized only six viruses from dogs with CIRD in the USA using metagenomics. These results indicated that the viral communities of CIRD in China were more complex and diverse than elsewhere.…”
mentioning
confidence: 99%